Identification of Splicing Quantitative Trait Loci (sQTL) in Drosophila melanogaster with Developmental Lead (Pb2+) Exposure - Qu, Wen; Gurdziel, Katherine; Pique-Regi, Roger; Ruden, Douglas M. (Frontiers in Genetics, 2017)
Lead (Pb) poisoning has been a major public health issue globally and the recent Flint water crisis has drawn nation-wide attention to its effects. To better understand how lead plays a role as a neurotoxin, we utilized the Drosophila melanogaster model to study the genetic effects of lead exposure during development and identified lead-responsive genes. In our previous studies, we have successfully identified hundreds of lead-responsive expression QTLs (eQTLs) by using RNA-seq analysis on heads collected from Drosophila Synthetic Population Resource. In this study, we focused our attention on alternative splicing events that are affected by lead exposure. We applied two methods in search for splicing QTLs (sQTLs) by using the RNA-seq data from control and lead-exposed Drosophila heads. First, we used the fraction of reads in a gene that falls in each exon as the phenotype. Second, we directly compared the transcript counts among the various splicing isoforms as the phenotype. Among the 1236 potential Pb-responsive sQTLs (p-value <0.0001, FDR <0.39), one of the most distinct genes is Dscam (Down Syndrome Cell Adhesion Molecule), which has tens of thousands of alternative splicing isoforms. In this paper, we show that splicing QTL analysis is a powerful tool to understand not only the association between the genome and splicing events, but also how genetic-related splicing changes after lead exposure. To our knowledge, this is the first paper that uses sQTL analyses to understand the neurotoxicology of an environmental toxin in any organism.